2015
DOI: 10.1061/(asce)me.1943-5479.0000301
|View full text |Cite
|
Sign up to set email alerts
|

Messy Talk in Virtual Teams: Achieving Knowledge Synthesis through Shared Visualizations

Abstract: Engineering teams collaborating in virtual environments face many technical, social and cultural challenges. In this paper we focus on distributed teams making joint unanticipated discoveries in virtual environments. We operationalize Dossick and Neff's definition of "Messy Talk" as a process in which teams mutually discover issues, critically engage in clarifying and finding solutions to the discovered issues, exchange their knowledge, and resolve the issue. Can globally distributed teams use "Messy Talk" via… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
43
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 30 publications
0
43
0
Order By: Relevance
“…AR/VR can also improve communication among stakeholders and provide better visualization for engineers, designers, and other stakeholders, enabling one-to-one fully immersive experience [18]. Furthermore, IVEs have the necessary potentials to achieve knowledge synthesis to improve the design process [19].Many industries implemented AR/VR in a successful way. For example, AR/VR has applications in manufacturing [20,21], retail [22,23], mining [24,25], education [26][27][28], and healthcare, especially for simulating surgeries [29][30][31].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…AR/VR can also improve communication among stakeholders and provide better visualization for engineers, designers, and other stakeholders, enabling one-to-one fully immersive experience [18]. Furthermore, IVEs have the necessary potentials to achieve knowledge synthesis to improve the design process [19].Many industries implemented AR/VR in a successful way. For example, AR/VR has applications in manufacturing [20,21], retail [22,23], mining [24,25], education [26][27][28], and healthcare, especially for simulating surgeries [29][30][31].…”
mentioning
confidence: 99%
“…AR/VR can also improve communication among stakeholders and provide better visualization for engineers, designers, and other stakeholders, enabling one-to-one fully immersive experience [18]. Furthermore, IVEs have the necessary potentials to achieve knowledge synthesis to improve the design process [19].…”
mentioning
confidence: 99%
“…discussion in online meetings, exchange of emails, 3D BIM models) may benefit collaborative interaction in the virtual team. Similarly, Dossick et al (2015) identified a gap of knowledge in the distributed design work of the virtual team and how to best support the virtual teams. The following section presents guidance to support international collaborative design projects, which aims to help to lower the perceived risk of collaboration in virtual teams.…”
Section: Discussionmentioning
confidence: 99%
“…Tucker & Rollo, 2006;Barry et al, 2012;Solnosky et al, 2014), but fewer include collaboration between students from two or more institutions from different geographical locations (such as Fruchter, 1999;Hussein & Peña-Mora, 1999;O'Brien et al, 2003 andBecerik-Gerber et al, 2012;Soetanto et al, 2014). Previous research studies have considered the effectiveness of distributed project teams (Gaudes et al, 2007;Kankanhalli et al, 2007) and the impacts of distance collaboration on the outcome of a design process (Dossick et al, 2015).…”
Section: Collaborative Design Projectmentioning
confidence: 99%
“…Moreover, the literature on BIM implementation encompasses standardizations (e.g., Eastman et al 2009;McCuen et al 2011), technical requirements (e.g., Dossick et al 2014;Gu and London 2010;Singh et al 2011), and organizational requirements (e.g., Ahn et al 2015;Son et al 2015;Taylor and Bernstein 2009). These aspects are confirmed in the BIM governance framework by Alreshidi et al (2017).…”
Section: Bim Workflowmentioning
confidence: 99%